Internal consistency and concurrent validity of the Montreal Cognitive Assessment in individuals with major depressive disorder - Srisurapanont M. (2017)
© 2017 Elsevier Ireland Ltd This study aimed to determine the internal consistency and concurrent validity of the Montreal Cognitive Assessment (MoCA), as well as its subtests, in patients with major depressive disorder (MDD). Participants were patients with DSM-IV MDD aged between 21 and 65 years. Neurocognitive function was assessed by using the MoCA and 12 neurocognitive tests. The composite z-score of 12 neurocognitive tests, which indicated the global cognitive performance, was calculated. Participants were 57 outpatients with MDD. Except the MoCA Orientation, each of the MoCA subtests showed a wide range of scores. The average inter-item correlation and the Cronbach's alpha of MoCA were 0.24 and 0.64, respectively. The MoCA total score was significantly and highly associated with the composite z-score of 12 neurocognitive tests (Pearson's r=0.78, p < 0.001). The score of each MoCA subtest was significantly and moderately correlated with the z-score of its analogous neuropsychological test (absolute Spearman's r s 's=0.33−0.56, p's≤0.01). The MoCA and its subtests are reliable and valid for assessing global and specific cognitive performance in patients with MDD and could be a tool for screening neurocognitive deficits in depressed patients.